Further development of the talent development environment questionnaire for sport - Li, C.; Wang, C. K. J.; Pyun, D. Y.; Martindale, R. (Journal of Sports Sciences, 2015)
Given the significance of monitoring the critical environmental factors that facilitate athlete performance, this two-phase research aimed to validate and refine the revised talent development environment questionnaire (TDEQ). The TDEQ is a multidimensional self-report scale that assesses talented athletes` environmental experiences. Study 1 (the first phase) involved the examination of the revised TDEQ through an exploratory factor analysis (n = 363). This exploratory investigation identified a 28-item five-factor structure (i.e., TDEQ-5) with adequate internal consistency. Study 2 (the second phase) examined the factorial structure of the TDEQ-5, including convergent validity, discriminant validity, and group invariance (i.e., gender and sports type). The second phase was carried out with 496 talented athletes through the application of confirmatory factor analyses and multigroup invariance tests. The results supported the convergent validity, discriminant validity, and group invariance of the TDEQ-5. In conclusion, the TDEQ-5 with 25 items appears to be a reliable and valid scale for use in talent development environments.